Effect of calcination temperature on the structural and electrochemical properties of Ni-rich materials - Luong, Vu Duc; Tung, Mai Thanh (Vietnam Journal of Chemistry, 2016)
LiNi0.8Co0.1Mn0.1O2 layered materials were synthesized by solid-state reaction using LiOH.H2O and hydroxide precursors of composition Ni0.8Mn0.1Co0.1(OH)2 (NMC) at various calcination temperature. The final LiNi0.8Co0.1Mn0.1O2 products showed different physical and electrochemical properties depending on their calcination temperatures. The LiNi0.8Co0.1Mn0.1O2 synthesized at 800 oC for 16 h showed the best electrochemical properties with a high discharge capacity over 188 mAh/g with a capacity retention > 96 % after 50 cycles at 1C-rate in a half cell. Keywords. Lithium ion batteries, Ni-rich material, co-precipitation, LiNi0.8Co0.1Mn0.1O2.